European political parties and European public space from the Maastricht Treaty to the Reg. No. 1141/2014 - Francesco Saitto (Europa-Kolleg Hamburg, Institute for European Integration, 2017)
The article, using a historical perspective, analyses the role and the functions of European political parties. Focusing on the different nature of national political parties and European political parties, the article describes the attempts to regulate political parties at the European level as a tool to enhance European democracy and to shape a European public sphere. In this perspective, the emerging role of political parties at the European level is analysed from the first election of the European Parliament, through the Tsatsos's Report. Subsequently, the Treaty of Nice and Regulation 2004/2003 are considered. Furthermore, the article focuses on the new regulation concerning political parties at the European level by taking into consideration Regulation n. 1141/2014. Moreover, the new Authority for European political parties and European political foundations and its powers are examined. Some final remarks concern the "lead candidates" innovation and the European electoral law.
Keywords: 320; European political parties; representative democracy; Regulation n. 1141/2014; Authority for European political parties; European public sphere